Praktik Toleransi Desa Pancasila Sebagai Penguatan Keharmonisan Antar Umat Beragama di Jawa Timur - Aris Shofa, Abd Mu'id (Universitas Negeri Malang, 2022)
This study aims to analyze the application of community tolerance values, harmonization patterns in religious plurality, as well as local actors who play a role in implementing tolerance in Pancasila Village. The method used in this study is descriptive qualitative. The research was conducted in Pancasila Village which is located in Situbondo, Blitar, Jember and Lamongan Regencies. The results of the study showed that the application of the tolerance value of the Pancasila Village community was seen from several activities, namely the culture of mutual cooperation in celebration events, construction of places of worship, and commemoration of religious holidays. The pattern of harmonization in religious plurality in Pancasila Village is visiting with polite ethics both verbally and non-verbally, inculcating tolerance from an early age by parents to children so that it becomes a habit, and not differentiating educational institutions based on religious background. Local actors in implementing tolerance in Pancasila Village are religious leaders, community leaders, village government, and youth leaders who work together to create harmony